(untitled) (St. Louis, Mo., 2013)
A quick, concise reference to the drugs and dosages used to treat exotic animals, Exotic Animal Formulary, 4th Edition addresses the most common questions and medical situations you encounter in clinical practice. Species covered include birds, fish, amphibians, reptiles, primates, wildlife, and all kinds of small mammals and "pocket pets." This edition is updated with a new chapter on invertebrates, information on the latest drugs, and a colorful new design. Written by clinical and research veterinarian James Carpenter, this book is the only drug formulary on the market created solely for the treatment of exotic animals.
Keywords: Exotic animals,Thuốc thú y,Động vật ngoại lai,Veterinary drugs; Liều dùng,Dosage